La alimentación y su incidencia en el rendimiento académico de los niños de la escuela “Machala” del cantón Latacunga provincia de Cotopaxi, en el periodo lectivo 2013-2014 - Escobar Guilcaso, Gabriela Alexandra (2015)
The present work is done with the purpose of contribute to create habits of diet at homes, and with it improve the student’s academic performance of the Machala School. The research has five chapters which permit us collect methods and techniques in order to design the model. Our experience in the educative area has contributed in the knowledge building that is our support as future teachers, with the purpose of incorporate a didactic methodology that contribute with the progress of the teaching learning process. The methodology used to the application of a workshop training program has facilitated obtains efficient information that allowed the development of the research work. Analyzing the problem, there are possible solutions that the institution must take with the purpose to improve the educative system.